KERAGAMAN HAMA PADA PERTANAMAN BAWANG MERAH (Allium ascalonicum L.) DI KABUPATAN PATI - Putri Mulia Azzumar; Siska Apriyani; Sri Wahyuni (JURNAL LITBANG PROVINSI JAWA TENGAH, 2021)
Shallots are one of the important commodities of high economic value in Indonesia. One of the obstacles in the production of shallots is the attack of pests and pathogens. The potential for yield loss due to pest and pathogen attacks can reach 20-100%. The research was carried out in the villages of Tegalarum, Sukorukun, and Sumberarum, Jaken District, Pati Regency from January to February 2021. The research used field observation methods, using swing nets to collect pests. This study aims to determine the types and diversity of pests in shallots cultivation in Jaken District, Pati Regency. The results of the research in the shallot plantations of Tegalarum and Sukorukun Villages found 3 species of pests, namely Liriomyza chinensis, Spodoptera exigua, and Bemisia tabaci. Meanwhile, in Sumberarum Village, 4 species of pests were found, namely Liriomyza chinensis, Spodoptera exigua, Bemisia tabaci, and Spodoptera litura. The diversity index (H') for Tegalarum and Sukorukun villages was low while Sumberarum villages were moderate. The evenness index (E) in the 3 villages is fairly evenly, while the species richness index (R) and dominance (D) for the three villages are low.